Influence of postharvest ultrasounds treatments on tomato (Solanum lycopersicum, cv. Zinac) quality and microbial load during storage - Pinheiro, Joaquina (2016)
Whole tomato fruits were treated at ultrasonic power levels from 10% to 100%, and at a constant frequency of 45 kHz, for different times (1-19 min). A central composite rotatable design (CCRD) was applied to optimise ultrasonic treatments for tomato quality (colour, texture and total phenolic content (TPC)) maintenance. According to response surface analysis, the optimal treatment parameters were 55%_10 min, 80%_15 min and 100%_19 min. At these conditions, and especially at higher power levels, a maximum retention of colour and texture, as well as an increase of TPC and microbial reduction were obtained in comparison with untreated fruits during 15 storage days at 10 degrees C. The ultrasounds treatment was found to be effective in delaying colour development and texture losses, preserving sensorial quality of whole tomato, with increase of TPC and microbial load reduction. Moreover, this postharvest treatment can be used as an alternative for extending fresh fruits shelf-life.